Recuperación que también fue final - Meyer, Lorenzo (El Colegio de México A.C., 2020)
This article presents a general analysis of the presidency of Enrique Peña Nieto, who came to power in 2012 as the result of the PRI victory following twelve years of PAN governments. From the outset a central and paradoxical element of the six-year administration is identified: the passage from a high-impact start to the term, with the “Pact for Mexico” and the emblematic reforms that emerged from this, to an end of term that saw the president’s popularity fall to historical lows, and his party suffer an unprecedented defeat. The paper considers the different structural reforms that derived from the Pact, examining the principal changes they brought about, together with the political dynamic that defined its implementation process. Meanwhile, emphasis is placed on two major factors that explain the decline in the image of both president and government: one, the numerous cases of corruption which not only implicated the president and his family but also several state governors from his party; secondly the spike in criminal violence and the failure of the policies aimed at fighting it.